Drying Characteristics of Rose Flowers - Raol, Jaydipsinh B.; Kumpavat, Mahendrasinh T.; Vyas, D. M. (Journal of Agricultural Engineering, 2014)
Full boom rose was dried by employing different drying methods such as hot air drying at 40, 50 and 60oC, microwave oven drying with silica gel at 50oC, vacuum drying at 40 oC and 760 mm Hg pressure besides solar and shade drying to find out the most suitable method and parameters. The Exponential and Page’s model were tested for their validity. Page’s model was found to fit best. The maximum and minimum drying time for rose flowers was 5 days in shade and 13 minutes in microwave oven. Drying of rose flowers under all treatments completely took place in the falling rate period. Maximum overall drying rate of 5.87 %/min was during microwave oven drying with silica gel at 50oC, followed by vacuum drying at 40oC. Microwave oven drying of rose flowers at 50oC with silica gel was found the best from the reduction in size point of view.